Evaluation of Plant Food Extracts in Experimental Model of Alzheimer's Like Disease Induced by Aluminum Lactate in Rats - Sahar Y. Al-Okbi, Doha A. Mohamed, Mohamed Abdel Fatah, Kholoud Abdel Aal, Shaimaa E Mohammed (Journal of Applied Pharmaceutical Science, 2017)
In the present research, the beneficial effect of plant food extracts in Alzheimer's like model, induced by aluminum, was studied in rats. A healthy control group without any treatments and a control with induced Alzheimer's like disease (ALD) were run. Tests groups of rats were treated with daily oral doses of methanol extract of Carica papaya leaves and fruits, Vitis venifera leaves and fruits, Origanum majorana herb, and petroleum ether extract of Carica papaya seeds separately for 5 weeks. Rats of test groups and control ALD received daily intraperitoneal injection of aluminum lactate starting from the 2nd week. Plasma and brain tissues were biochemically analyzed. Control rats with ALD demonstrated a significant increase in erythrocyte sedimentation rate, plasma malondialdehyde, nitrite, tumor necrosis factor - alpha and cholinesterase activity with significant reduction in plasma vitamin C and E compared to control healthy rats. Brain malondialdehyde and acetyl cholinesterase activity showed significant elevation in control rats with ALD. The studied plant extracts showed efficient inhibition of oxidative stress, inflammation, and cholinesterase activity in plasma and brain with variable degrees. Both brain oxidative stress and acetyl cholinesterase activity were reduced by methanol extracts of Vitis venifera and Carica papya fruits.
Keywords: Plant food extracts, Alzheimer's like disease, aluminum lactate, acetyl cholinesterase, inflammatory biomarker, oxidative stress.